If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4s + 5)(3s + 8s + -9) = 0 Reorder the terms: (5 + 4s)(3s + 8s + -9) = 0 Reorder the terms: (5 + 4s)(-9 + 3s + 8s) = 0 Combine like terms: 3s + 8s = 11s (5 + 4s)(-9 + 11s) = 0 Multiply (5 + 4s) * (-9 + 11s) (5(-9 + 11s) + 4s * (-9 + 11s)) = 0 ((-9 * 5 + 11s * 5) + 4s * (-9 + 11s)) = 0 ((-45 + 55s) + 4s * (-9 + 11s)) = 0 (-45 + 55s + (-9 * 4s + 11s * 4s)) = 0 (-45 + 55s + (-36s + 44s2)) = 0 Combine like terms: 55s + -36s = 19s (-45 + 19s + 44s2) = 0 Solving -45 + 19s + 44s2 = 0 Solving for variable 's'. Factor a trinomial. (-5 + -4s)(9 + -11s) = 0Subproblem 1
Set the factor '(-5 + -4s)' equal to zero and attempt to solve: Simplifying -5 + -4s = 0 Solving -5 + -4s = 0 Move all terms containing s to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -4s = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -4s = 0 + 5 -4s = 0 + 5 Combine like terms: 0 + 5 = 5 -4s = 5 Divide each side by '-4'. s = -1.25 Simplifying s = -1.25Subproblem 2
Set the factor '(9 + -11s)' equal to zero and attempt to solve: Simplifying 9 + -11s = 0 Solving 9 + -11s = 0 Move all terms containing s to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -11s = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -11s = 0 + -9 -11s = 0 + -9 Combine like terms: 0 + -9 = -9 -11s = -9 Divide each side by '-11'. s = 0.8181818182 Simplifying s = 0.8181818182Solution
s = {-1.25, 0.8181818182}
| 3c+4=11 | | 9x-5x^2=-2 | | 3+4=11 | | (x-2)(x+2x+4)=0 | | 9k-4=23 | | p+2=9 | | 3c+7=10 | | 2(m-3)(m-3)+2m^2+12m=-3m^2+5 | | 18+7x(32-16)= | | 4(d-9)+3(2d+8)=32 | | 6v-=42 | | 5=13-k | | (w+2)(w+2)-2(w+2)+9w=8 | | (5r-7s)(4r+3s)=0 | | .67(6h+3)=.33(3h-4)-h^2 | | (5r-7s)(4r+3s)=3 | | x^2+7x+49=0 | | 5w-3=12 | | 2b+3(3)=10 | | 4(d-5)+20=5-2d | | 2x=5y+13 | | (2a+3b)(5a-2b)=0 | | 8(2w-6)+4(-1-5w)=o | | (5y-3)(y+2)=0 | | 2.3=1.7+m | | 25=x^2+36 | | y-5=4 | | 2x-14=3(x+3)(x+3)-8x^2 | | y=6x+2 | | -6(x-2)+4(3-6x)=36 | | y^2-6+3y=4(y-5)(y-5)-12 | | (7y-1)(2y-3)=0 |